Patients with small acetabular cartilage defects caused by femoroacetabular impingement do not benefit from microfracture - Riedl, Moritz; Banke, Ingo; Goronzy, Jens; Sobau, Christian; Steimer, Oliver; Thier, Steffen; Zinser, Wolfgang; Henßler, Leopold; Alt, Volker; Fickert, Stefan (Journal of Clinical Medicine, 2022)
Objective: According to current recommendations, large cartilage defects of the hip over 2 cm2 are suggested to undergo autologous chondrocyte transplantation (ACT), while small defects should be treated with microfracture. We investigated if patients with small chondral defects of the hip joint (≤100 mm2) actually benefit from microfracture. Design: In this retrospective multicenter cohort study 40 patients with focal acetabular cartilage defects smaller than 100 mm2 and of ICRS grade ≥2 caused by femoroacetabular impingement were included. Twenty-six unrandomized patients underwent microfracture besides treatment of the underlying pathology; in 14 patients cartilage lesions were left untreated during arthroscopy. Over a mean follow-up of 28.8 months patient-reported outcome was determined using the iHOT33 (international hip outcome tool) and the VAS (visual analog scale) for pain. Results: The untreated group showed a statistically significant improvement of the iHOT33 after 12 (p = 0.005), 24 (p = 0.019), and 36 months (p = 0.002) compared to the preoperative score, whereas iHOT33 in the microfracture group did not reveal statistically significant changes over time. There was no significant difference between both groups on any time point. Regarding pain both groups did not show a significant improvement over time in the VAS. Conclusion: The subjective outcome of patients with small cartilage defects of the hip (≤100 mm2) improves 12 months after arthroscopic FAIS surgery without any cartilage treatment. However, no improvement could be seen after microfracture. Therefore, a reserved surgical treatment for small cartilage defects of the hip under preservation of the subchondral bone is recommended especially if a simultaneous impingement correction is performed.
Gesehen am 24.07.2023